2017
DOI: 10.1097/dcr.0000000000000841
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Animal Models Used in Research of Origins and Treatments of Fecal Incontinence

Abstract: Validated animal models representing the main etiologies of fecal incontinence exist, but no animal model to date represents the whole pathophysiology of fecal incontinence. Therefore, the individual research questions still dictate the choice of model and species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…After dissection, the sphincter wound was repaired with interrupted sutures using 5-nylene ( Figure 1 ). The IAS specimen was harvested near the anal verge via removal from the distal rectum 1 week after cryoinjury, while considering the different myogenic features of SMCs in the IAS from those in the rectum [ 2 , 25 ]. After harvesting, all experimental animals were euthanized using carbon dioxide gas.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After dissection, the sphincter wound was repaired with interrupted sutures using 5-nylene ( Figure 1 ). The IAS specimen was harvested near the anal verge via removal from the distal rectum 1 week after cryoinjury, while considering the different myogenic features of SMCs in the IAS from those in the rectum [ 2 , 25 ]. After harvesting, all experimental animals were euthanized using carbon dioxide gas.…”
Section: Methodsmentioning
confidence: 99%
“…Regenerative medicine using cells has evolved as an optional treatment for anal incontinence (AI) [ 1 ]. According to previous systematic reviews of AI cell therapy, most experimental studies have been performed using animal models associated with injury or damage to the external anal sphincter (EAS) or a nerve [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, FI cell treatments [ 16 - 19 ] using bone mesenchymal stem cells (MSCs), adipose stem cells (ASCs), myoblasts, and a combined treatment strategy [ 20 - 24 ] have been reported functional improvement in the injured sphincter. However, these studies for cell therapy showed a bias and lacked data for clinical use as reported by the previous systematic reviews [ 25 - 27 ]. Data on the regeneration of IAS associated with basal tone was also limited, and most cell therapy studies were performed on animal models for the skeletal muscle of EAS or nerve damage [ 25 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies for cell therapy showed a bias and lacked data for clinical use as reported by the previous systematic reviews [ 25 - 27 ]. Data on the regeneration of IAS associated with basal tone was also limited, and most cell therapy studies were performed on animal models for the skeletal muscle of EAS or nerve damage [ 25 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%